Internal controls, corporate governance and fi nancial performance of MFIs in Uganda - Abanis, Turyahebwa; Byamukama, Eliab Mpora; Arthur, Sunday (Kabale University Interdisciplinary Research Journal (KURJ, 2023)
The article reconnoitered the rapport between internal controls, corporate governance and financial performance of MFIs in Uganda a case of Central Uganda. The study adopted a descriptive, cross-sectional and correlational design. The study covered 76 MFIs in Uganda with 332 respondents. The findings argument to a significant positive relationship between internal controls, corporate governance and financial performance of MFIs. Internal Controls and financial performance of MFIs (r = 0.651, P-value = 0.000), corporate governance and financial performance of MFIs (r = 0.562, P-value = 0.000). From the results, we sanction that internal controls, corporate governance, predict over 70.2% of the change in financial performance of Micro Finance Institutions in Uganda. The findings display a good model fit and fig.2 defines the model of internal controls and corporate governance on financial performance of MFIs in Uganda and is comprised of 3 magnitudes of Internal Controls in terms of Control Environment, Control Activities, Risk Assessment as well as corporate governance and their predictive power on financial performance of MFIs in Uganda. Figure 2 and table 1 and 2 clearly indicate that Internal Controls and Corporate Governance are significantly associated with financial performance of MFIs. The study spoke to pragmatic issues that have not been shielded in the literature, more especially in the microfinance industry Uganda. Besides, the study has attempted to negate or confirm whether the theoretical underpinnings are empirically supported in Microfinance Institutions in Uganda. Consequently, the study has underwritten to the lasting internal controls and corporate governance debate in the field of financial industry. The study has further established that internal control and corporate governance magnitudes operate in a synergic way to affect financial performance in Microfinance Institutions in Uganda.